Devoloping Lifelong Learning : The Role Of The Academic Liaison Librarians In An International Islamic University - Hassan, Basri (2015)
Librarians in tertiary education have a common goal of providing learning opportunities to their library clients. Academic Liaison Librarians work with academics, researchers and students to help them achieve their research, learning and teaching goals. They ensure that the library collection supports the research and teaching needs of the university community. They conduct information literacy skills classes (in teaching labs) incorporating hands-on training to help clients used the online databases, e-books and printed resources provided by the library; and also help their clients manage research citations. International Islamic University Malaysia (IIUM) library served a large population of university community coming from many countries around the world. The main library in Gombak campus has large collections of resources (online, electronic, printed and non-printed) ranging from many disciplines. The liaison librarians are tasked with developing lifelong learners to face the challenges posed by the digital revolution.